Antenatal Surveillance in Twin Pregnancies Using the Biophysical Profile. (9th October 2015) - Booker, Whitney; Fox, Nathan S.; Gupta, Simi; Carroll, Rachel; Saltzman, Daniel H.; Klauser, Chad K.; Rebarber, Andrei
Abstract : Objectives: The nonstress test is currently the most widely used modality for antenatal surveillance in twin pregnancies, with a quoted false‐positive rate of 11%–12%. Our objective was to report our experience with the sonographic portion of the biophysical profile in twin pregnancies as the primary screening modality. Methods: Women with twin pregnancies delivered by a single maternal‐fetal medicine practice from 2005 to 2013 were included. We excluded monoamniotic twins. Twin pregnancies began weekly sonography for the biophysical profile starting at 32 to 33 weeks, or earlier if indicated. The nonstress test was performed if the sonographic biophysical profile score was less than 8 of 8. We reviewed biophysical profile scores and outcomes for all patients who delivered at 33 weeks or later to assess the false‐positive rate for the biophysical profile, as well as the incidence of intrauterine fetal death (IUFD) after initiation of antenatal surveillance. Results: A total of 539 twin pregnancies were included. The incidence of IUFD per patient was 2 per 539 (0.4%; 95% confidence interval [CI], 0.1%–1.3%), and the incidence of IUFD per fetus was 2 per 1078 (0.19%; 95% CI, 0.05%–0.7%). The overall positive screen rate was 24 per 539 (4.45%; 95% CI, 3.0%–6.5%). The false‐positive screen rate, defined as an abnormal biophysical profile that did not diagnose an IUFD or lead to delivery, was 10 per 539 (1.9%; 95% CI, 1.0%–3.4%). Conclusions—In twin pregnancies the use of the sonographic biophysical profile for routine antenatal surveillance has a low false‐positive rate, with a very low incidence of IUFD. The sonographic biophysical profile should be considered as a primary mode for antenatal surveillance in twin pregnancies, with a reflex nonstress test for an abnormal score.